Religious moderation in the community of the Tariqah Qodiriyah Naqshabandiyah of Suryalaya - Santoso, Try Riduwan; Salahudin, Asep; Munawar, Asep Hamdan; Rahayu, Rizqi; Munggaran, Nita Anjung (International Journal of Nusantara Islam, 2025)
Religious moderation is an effort by the government to form a harmonious religious group order in Indonesia. The purpose of this study is to analyze how the community of tariqah practitioners implements religious moderation in religious and state life. This study uses a descriptive qualitative approach. Data collection was carried out through observation, interviews, and documentation. The results of this paper are that the TQN Suryalaya community is known as a moderate group and has obedience to religious and state rules. The basic foundation in strengthening obedience to religious and state rules is stated in the Tanbih which is always read in the rituals of the TQN Suryalaya community. The impact of practicing the teachings of TQN is able to form humans who have an attitude of solidarity, tolerance, cooperation and respect for all groups as a form of God's love for His creatures. The doctrine of tariqah also has implications for self-awareness and peace of mind so that humans achieve living in harmony in diversity. This paper recommends that the practice of religious moderation in the tariqah community has a uniqueness that is formed through the practice of tariqah teachings and the exemplary behavior of a Murshid.